5 - Questions du genre liées aux conflits fonciers: impact sur la production durable des vivriers au Sud-Bénin: 10.4314/ad.v26i2.22144 - Sohinto , David (Africa Development, 2001)
Abstract: Food crops cannot be dissociated from an analysis of gender-related problems linked to land conflicts in Southern Benin. Indeed, a serious crisis is going on there. In connection with those conflicts, the author highlights the land discrimination against women, despite the fact that they are those who provide food to the constantly growing Béninois population. Such a discrimination expresses itself through an unequal sharing t^f inheritance between the sons and daughters of land owners, based on the patrilineal nature of this society. But, it is difficult to identify the indicators of such discrimination, and also difficult to measure the impact of the structural violence it triggers off. However, women resort to alternative solutions, such as share tenancy, donations (father giving plots of land to his daughters in his lifetime), borrowing of plots of land from members of the family etc.